The Heritage of Ivan Fedorov in the Research Projects of Siberian Archeographers - I. A. Shilova; E. A. Yudina (Библиосфера, 2024)
The history of studying Ivan Fyodorov heritage in Siberia is connected with the expedition finds of Novosibirsk archeographers – researchers of the SPSTL RAS and Novosibirsk State University (NSU). An important component of this work was the cameral one in the archives of Siberia and the Far East, which has led to the identification of book monuments of the XVI cent., representing copies of publications of Russian first printers, and their detailed study. The purpose of the article is to present significant discoveries of Novosibirsk archaeographers related to the initial stage of Russian book printing, to summarize the results of the conference «The Legacy of Ivan Fedorov in the Siberian land». Research results are: the significant publications of Novosibirsk archeographers are based on work with copies of Cyrillic editions of the initial period of printing stored in the SPSTL RAS. The discovery in 2023 of the fifth exemplar of the Psalter with the Book of Hours of 1570 is understood as a natural result of the archaeographic work of the researchers of the Rare Books and Manuscripts Department of the SPSTL RAS. The review of the reports of the conference «The Legacy of Ivan Fedorov in the Siberian Land», organized by the SPSTL RAS together with with the Novosibirsk Orthodox Theological Seminary in connection with the discovery of a n ew copy of the Russian first printer.